2015
DOI: 10.1016/j.chemosphere.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sub-lethal effects of orchard-applied pyrethroids using video-tracking software to quantify honey bee behaviors

Abstract: Evaluating sub-lethal effects of orchard-applied pyrethroids using video-tracking software to quantify honey bee behaviors" (2015). Faculty Publications: Department of Entomology. 377.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…Pyrethroids are also commonly used in crop protection against various insects considered as pests . According to related reports, single‐crop pollination requires 1.6 million bee colonies to provide services, while pyrethroids are used in nearly 1 million acres of orchard (including apples, apricots, sweet and tart cherries, peaches, plums, prunes, pears, and nectarines) in the USA . Cypermethrin and deltamethrin are the two most common pyrethroid insecticides .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrethroids are also commonly used in crop protection against various insects considered as pests . According to related reports, single‐crop pollination requires 1.6 million bee colonies to provide services, while pyrethroids are used in nearly 1 million acres of orchard (including apples, apricots, sweet and tart cherries, peaches, plums, prunes, pears, and nectarines) in the USA . Cypermethrin and deltamethrin are the two most common pyrethroid insecticides .…”
Section: Introductionmentioning
confidence: 99%
“…41 According to related reports, single-crop pollination requires 1.6 million bee colonies to provide services, while pyrethroids are used in nearly 1 million acres of orchard (including apples, apricots, sweet and tart cherries, peaches, plums, prunes, pears, and nectarines) in the USA. 42 Cypermethrin and deltamethrin are the two most common pyrethroid insecticides. 43 A study found that deltamethrin did not alter certain genes related to immune function, while cypermethrin had negative effects on the transcription of certain immune system genes in bees.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary effects can cause damage to adult bees, such as disorientation, which could compromise their return to the colony (Ingram et al, 2015;Silva et al, 2016). Furthermore, bees could transport the chemical products to colonies, accumulating pesticides in the food, which suggests poisoning the larvae when fed with these contaminated products (Johnson et al, 2010;Martinello et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous convergent observations show that chemical control has important effects on pollinating insects, which suffer immediate or delayed losses that affect adults or larvae (Carvalheiro et al, 2013)). Pyrethroids have been reported to pose repellency which alters foraging behavior with the benefit of preventing bees from encountering a lethal dose in the field (Ingram et al, 2015). However, sub-lethal exposure to pyrethroids may adversely impact bee behavior potentially resulting in social dysfunction or disruption of foraging (Ingram et al, 2015).…”
Section: Introductionmentioning
confidence: 99%